Relationship between psoriasis and non-alcoholic fatty liver disease - Narayanasamy, Krishnasamy; Sanmarkan, Abarna Devi; Rajendran, Karthick; Annasamy, Chezhian; Ramalingam, Senthilkumar (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Various components of metabolic syndrome have an important role in the pathogenesis of both Non-alcoholic fatty liver disease (NAFLD) and psoriasis, suggesting an association between these diseases. However, at present very few studies have reported on the systematic evaluations of the prevalence of NAFLD in patients with psoriasis disorder. Aim: To investigate the prevalence of NAFLD in patients with psoriasis vulgaris. The study also evaluated the parallel relationship between both of the diseases. Material and methods: Patients over18 years old and with a diagnosis of psoriasis vulgaris at the outpatient unit of Department of Dermatology were considered for enrolment and were followed up by the Department of Hepatology, Madras Medical College. Each and every patient completed a questionnaire, underwent a thorough skin evaluation, and had a right upper quadrant ultrasound and fasting blood workup. Results : Two hundred and fifty patients were enrolled in the study. The participants were predominantly middle aged (mean: 44.74 ±11.989 years), overweight (average body mass index (BMI): 24.772 ±3.611 kg/m2), and male (68%, n = 170). The overall prevalence of NAFLD among psoriasis was 45.2%. Conclusions : Non-alcoholic fatty liver disease is highly prevalent among our cohort of patients with psoriasis, occurring in 45.2% of patients. Comorbidity of NAFLD is highly associated with psoriasis, which emphasises that both diseases may develop simultaneously. Health care providers should be mindful of this association since early evaluation and diagnosis of NAFLD in patients with psoriasis may play a vital role in alleviating the progression of liver disease.